Protective effects of menthol against sepsis-induced hepatic injury: Role of mediators of hepatic inflammation, apoptosis, and regeneration - Matouk, Asmaa I.; El-Daly, Mahmoud; Habib, Heba A.; Senousy, Shaymaa; Naguib Abdel Hafez, Sara Mohamed; Kasem, AlShaimaa W.; Almalki, Waleed Hassan; Alzahrani, Abdulaziz; Alshehri, Ahmed; Ahmed, Al-Shaimaa F. (Frontiers in Pharmacology, 2022)
Liver dysfunction in sepsis is a major complication that amplifies multiple organ failures and increases the risk of death. Inflammation and oxidative stress are the main mediators in the pathophysiology of sepsis. Therefore, we investigated the role of menthol, a natural antioxidant, against sepsis-induced liver injury in female Wistar rats. Sepsis was induced by cecal ligation and puncture (CLP). Menthol (100 mg/kg) was given intragastric 2 hours after CLP. Blood samples and liver tissues were collected 24 hours after surgery. Menthol significantly (p <0.05) attenuated the sepsis-induced elevation in serum liver enzymes and improved the hepatic histopathological changes. Menthol treatment significantly (p <0.05) decreased hepatic levels of tumor necrosis factor-alpha, malondialdehyde, total nitrite, and cleaved caspase-3. It restored the hepatic levels of superoxide dismutase and reduced glutathione. Additionally, menthol significantly (p <0.05) increased hepatic levels of B-cell lymphoma 2 (Bcl-2); an anti-apoptotic factor, and proliferating cell nuclear antigen (PCNA), a biomarker of regeneration and survival. Our results showed the therapeutic potential of menthol against liver injury induced by sepsis.